Implementasi E-Democracy pada Tingkat Program Studi: Transformasi Praktik Demokrasi Mahasiswa dalam Pemilihan HMPS PGSD di Universitas Nias - Zai, Eka Periaman; Lase, Indah Wijaya (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the implementation of e-democracy and the quality of student participation in the election of the Head of the Student Association of the Elementary School Teacher Education Study Program (HMPS PGSD) at Nias University. The research uses a qualitative approach with a case study design. Data were collected through in-depth interviews with the election committee, HMPS chair candidates, and student voters, limited observation of the election process, and a study of documentation of the election based on the University of Nias' Integrated Academic Information System (SIMAT). Data analysis was conducted using an interactive analysis model that included data reduction, data presentation, and conclusion drawing, and was reinforced with source and method triangulation to maintain data validity. The results showed that the implementation of e-democracy through SIMAT increased the efficiency, transparency, and accessibility of student participation because voters could exercise their voting rights without being bound by space and time. However, the quality of student participation is still dominated by procedural and symbolic aspects, while deliberative involvement is relatively limited. The lack of interactive dialogue space, low digital democracy literacy, and the dominance of e-voting mechanisms mean that e-democracy is not yet optimal as a means of learning democracy.